Red and White Cooperative: Challenges and Opportunities for Implementation in Manggarai Regency - Vianney, Yohanes Mario; Larum, Kordianus (Westscience Press, 2025)
Presidential Instruction of the Republic of Indonesia Number 9 of 2025 launched the national program